Maxent modeling for predicting the potential distribution of Arbutus andrachne L. belonging to climate change in Turkey. - SARIKAYA, AYSE GUL; ORUCU, Omer Kamil (Kuwait Journal of Science, 2021)
Arbutus andrachne L. Turkey, which grows naturally in Turkish flora and a species with a wide range use areas with its wood like decorative purposes, packaging, chairs and also fruits are consumed as non-wood forest products. This study was conducted to determine effects of climate change on Arbutus andrachne, which is used as an important non-wood forest product. For this purpose, RCP 4.5 and RCP 8.5 climate change scenarios for 2050 and 2070 determined and potential distribution areas were presented. According to climate scenarios in 2050 and 2070, it was determined that the distribution of Arbutus andrachne will decrease in the southern regions of Turkey. Although the spread of the species will increase in the western and northern regions, the potential habitat losses will reach serious proportions.